Harmful Effects of Lead on Learning - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Members of the Depts. Community Medicine, Education, Geology, and Med. Statistics Unit, Univ. Edinburgh, have investigated the effect of blood-lead on cognitive ability and educational attainment in a sample of 855 boys and girls aged 6-9 years from 18 primary schools in central Edinburgh.